Chromane isolated from leaves of Dillenia indica improves the neuronal dysfunction in STZ-induced diabetic neuropathy. (12th July 2017) - Kaur, Navpreet; Kishore, Lalit; Singh, Randhir
Abstract: Ethnopharmacological relevance: According to the Indian traditional medicine, Dillenia indica L. has shown therapeutic efficacy in various diseases. Fruits and leaves of the plant possess anti-oxidant and anti-inflammatory properties. Reactive oxygen species, formation of advanced glycation end products (AGEs) and apoptosis are implicated in the pathogenesis of diabetic neuropathy. Aim of the study: The aim of the present study was to explore the effect of D. indica and its isolate, chromane (CR), on thermal and mechanical hyperalgesia, allodynia, MNCV and oxidative-nitrosative stress in streptozotocin-induced experimental diabetes. Material and methods: Diabetes was induced by intraperitoneal administration of Streptozotocin (STZ; 65 mg/kg) for the development of diabetic neuropathy. Chronic treatment with DAE (100, 200 and 400 mg/kg, p.o. ) and CR (5 and 10 mg/kg, p.o. ) for 30 days was started from the 60th day of STZ administration. Development of neuropathy was evident from a marked hyperalgesia and allodynia; reduced MNCV associated with increased formation of AGEs and reactive oxygen species. Results: significantly attenuated behavioral and biochemical changes associated with diabetic neuropathy. Present study suggested that DAE and CR ameliorated hyperglycemia and diabetic neuropathic pain via modulation of oxidative-nitrosative stress and reduction in AGEs formation in the diabetic rats. Conclusion: Thus D. indica might be beneficial in chronic diabetics, ameliorate the progression of diabetic neuropathy and may also find application in diabetic neuropathic pain. Graphical abstract: